Фітогормональна та трофічна регуляція яровизаційного процесу озимої м’якої пшениці in vivo та in vitro - Чумакова, Вікторія Володимирівна; Chumakova, Victoria V. (Харків : Харківський національний університет імені В.Н. Каразіна, 2021)
Chumakova V.V. Phytohormonal and trophic regulation of the vernalization process of winter wheat in vivo and in vitro. - Manuscript. Thesis for a Candidate Degree in Biology, Speciality 03.00.12 – Рlant physiology. – V.N. Karazin Kharkiv National University of the Ministry of Education and Science of Ukraine. – Kharkiv, 2021. The dissertation is devoted to find out the allelic state of Vrn genes, the patterns of vernalization processes in soft winter wheat sprouts under contrasting conditions of trophic support, as well as the priming of gibberellin (GA) under these conditions. The allelic state of Vrn genes in vitro, their effects on morphogenesis during vernalization and the influence of GA on morphogenetic processes in callus of winter wheat varieties have been studied. The winter soft wheat varieties were used. There were Statna, Doridna, Alians, Astet, Myronivska 808 and Olvia, and the near-isogenic lines by Vrn genes (NILs), created in the genotype of winter varieties Myronivska 808 and Olvia. Depending on the tasks of the study, seeds, sprouts and callus culture were used.
Phytohormonal and trophic regulation of the vernalization process of winter wheat in vivo and in vitro
Робота присвячена з’ясуванню алельного стану генів Vrn, закономірностей перебігу яровизаційних процесів у проростках пшениці м’якої озимої на фоні різного трофічного забезпечення, а також за праймування гібереліном. Досліджені алельний стан генів Vrn у культурі in vitro, їх ефекти на морфогенез за яровизації та вплив ГК на морфогенетичні процеси у калусах. У алельному стані генів VRN у ізогенних ліній пшениці виявлені відмінності, які обумовлювали різні темпи розвитку рослин. Природне і штучне трофічне забезпечення проростків на 45-ту добу яровизації зумовлювало зміну алельного стану гену Vrn-B1b. Різний рівень трофічного забезпечення яровизації і ГК на його фоні визначав інтенсивність ростових процесів, проліферації клітин, обміну вуглеводів та темпи розвитку рослин.
Keywords: Research Subject Categories::NATURAL SCIENCES::Biology; пшениця м’яка (Triticum aestivum L.); ізогенні лінії; гени Vrn; гіберелін; яровизація; трофічне забезпечення; культура in vitro; темпи розвитку; soft wheat (Triticum aestivum L.); isogenic lines; Vrn genes; gibberellin; vernalization; trophic support; in vitro culture; rates of development